Case study: Comprehensive rehabilitation of a patient with chondrosarcoma after post-resection arthroplasty with reconstruction of the sacroiliac joint and the rear pelvic column using the Custom Made MUTARS prosthesis in 3D technology - Szczypiór-Piasecka, Karina; Wrzalik, Łukasz; Antczak, Krzysztof; Mińko, Alicja (Journal of Education, Health and Sport, 2021)
Introduction: Sarcomas are a group of malignant neoplasms occurring relatively rarely. Chondrosarcoma (chondrosarcoma) is a connective tissue cancer. It is located in the femur and brachial bones most often, and is less common in the ribs and pelvis. It occurs between the fourth and sixth decades of life. Treatment requires resection of diseased tissue and reconstruction of the bone defect. Chemotherapy or radiotherapy is used only in case of disqualification from surgery. An inherent element of the treatment is rehabilitation, which should start from the first day after the surgery. The aim of the work was to present a personalized rehabilitation program for the patient after reconstruction of the sacroiliac joint and the rear pelvic column using the Custom Made MUTARS endoprosthesis in 3D technology, taking into account the latest physiotherapeutic methods. The patient underwent surgery at the Chair and Department of Orthopedics, Traumatology and Oncology of the Motor Organ due to the chondrosarcoma of the hip bone. Conclusions: 1. Early physiotherapy significantly accelerates the return of functional capacity. 2. Modern methods of physiotherapy such as osteopathy and manual therapy are an inherent element of comprehensive treatment of people after bone reconstruction. 3. Comprehensive, early physiotherapy improves the psychophysical condition of patients after treatment of bone tumors.